THE RELATIONSHIP AMONG KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF DIETARY, AND THE INCIDENCE OF ANEMIA ON ADOLESCENT GIRLS - Citra Algiatie Subagja; Ariani Fatmawati; Nina Gartika (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
Anemia in adolescent girls is quite high. According to the World Health Organization (WHO), the prevalence of anemia in adolescent girls around 53,7%. The impact of anemia on adolescent girls is drowsy, lack of concentration, lethargic, and dizziness in the learning time. This study aimed to determine the relationship of dietary knowledge, attitudes, and behavior level and the incidence of anemia on adolescent girls in Kemala Bhayangkari Junior High School. The study design used quantitative analytic with a cross-sectional design. The sample was taken by the consecutive sampling method. The samples were 134 respondents. Data analysis used the Spearman rank correlation test .The results showed that adequate dietary knowledge (48.5%), positive dietary attitude (59.7%), positive dietary behavior (56.0%), and anemia (18.7%) with a value for knowledge p = 0.803, attitude p = 0.973 and behavior p = 0.997. It can be concluded that there is no relationship among of dietary knowledge, attitudes, and behavior level and the incidence of anemia on adolescent girls with anemia in Kemala Bhayangkari Junior High School Bandung. It is suggested for adolescent girls that they needs to increase the consumption of nutritious foods, foods with high in iron, and consume iron supplements, especially during menstruation.